PERSPECTIVE—Pragmatism in Organization Studies: Meeting the Challenges of a Dynamic and Complex World - Farjoun, Moshe; Ansell, Christopher; Boin, Arjen (Organization Science, 2015)
Organizational scholars have shown a growing interest in drawing on the philosophy of Pragmatism to address contemporary problems and theoretical questions. We elucidate Pragmatism’s core ideas and show their uniqueness and relevance to the field. We present Pragmatism as a problem-solving philosophy that builds on a rich and behaviorally plausible model of human nature, views reality in terms of processes and relations, and highlights the interplay of meaning and action. We demonstrate how Pragmatist ideas can help transcend the perennial problem of agency and structure and illustrate how these ideas might contribute to one specific domain of research on categories and categorization. More generally, Pragmatism is well suited to understanding the contemporary challenges of change and complexity especially as they play out across multiple levels of analysis. We argue that Pragmatism provides a “third way” between rational and structural approaches and represents a living school of organization theory in its own right.